PERAN LINGKUNGAN SEKOLAH TERHADAP MINAT BELAJAR SISWA SD/ MI - ZAENOL FAJRI (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2019)
National education is organized through formal, informal and non-formal education. National education targets will be achieved if the purpose of learning achieved properly. The implementation of learning is influenced by internal and external factors. One example of internal factors is interest to learn and externals is the school environment. The school environment consists of educators and education personnel, teaching materials, fellow students and the physical environment (facilities and infrastructure). a good school environment in accordance with the standardization of education, it can increase student learning interest and facilitate the implementation of conducive learning. So that the purpose of learning can be achieved well and smoothly. In conclusion, that the influence of the school environment can have a positive impact on learning interest so that learning objectives can be achieved well and smoothly.